PENGEMBANGAN PLATFORM WEB LAYANAN OUTSOURCING DAN MANAJEMEN KARYAWAN: Pengembangan Platform Website Layanan Outsourcing Manajemen Karyawan PT.Buntariva Mitra Solusi - Chinoble Cofely; Desi Ramayanti (JSAI (Journal Scientific and Applied Informatics), 2025)
PT. Buntariva Mitra Solusi, which is engaged in providing services, faces significant problems due to the use of manual systems in managing service requests, employee data, and evaluating service provider performance, which causes delays in the process and decreases the level of client trust. This study aims to design and implement an integrated web platform that is able to automate and unify all of the company's main business processes, including service request management, employee data management, contract arrangements, and real-time monitoring and evaluation of service provider performance. The development method applied is the Software Development Life Cycle (SDLC) with a waterfall model, which allows for systematic and structured project management. The platform implementation is carried out using the PHP programming language, MySQL database, and Apache as a web server. System testing is carried out using the Black Box method to ensure that all functions run according to specifications without any significant errors. The test results show that the system can increase transparency, speed up operational processes, and provide easy access to information for management and clients.